IMAGES OF THE NOVEL "EREVON" - Muhiddinova (Abdullayeva) Dilafruz Mansurovna (Galaxy International Interdisciplinary Research Journal, 2022)
The following article provides information that the discovery of Erevon is based on Butler’s colonial experience; The book was translated into Dutch in 1873 and into German in 1897. To publish this book as the author of Erevon would be to abandon irony and satire. Also, all the images of the work with their metaphorical descriptions and actions in the process of the development of events are widely disclosed.